Optimization of Encryption Algorithm for Secured Communication - Kumar, Ajay (My University, 2014)
Data security is an essential component of an organization in order to keep the information safe from various competitors. It helps to ensure the privacy of a user from others. Secured and timely transmission of data is always an important aspect for organization. Strong encryption algorithms and optimized key management techniques always help in achieving confidentiality, authentication and integrity of data and reduce the overheads of the system. Keeping in view the importance of dynamic keys for secure data transmission this work is carried out to optimize an encryption algorithm based upon dynamic key. Literature Survey has been carried out by incorporating key papers related to data encryption. From the literature survey gaps and observation have also been drawn. Encryption algorithm by Hill cipher was critically analyzed and key management has also been optimized. In proposed algorithm simulation results have been achieved using MATLAB 7.3 and proves that the algorithm is optimized in comparison to another Hill cipher technique in term of hacking and processing time. Finally, conclusion and future scope of work has also been stated the end of this thesis
M.E. (ECED)
Keywords: encryption algorithm,decryption algorithm; key,pliantext